A systematic review of electronic multi‐compartment medication devices with reminder systems for improving adherence to self‐administered medications. (1st February 2016) - Paterson, Mary; Kinnear, Moira; Bond, Christine; McKinstry, Brian
Abstract: Background: Many patients experience difficulties adhering to medication regimes. For people who forget or get confused about medication, there are products to help them such as multi‐compartment medication devices (MMDs). Some of these, known as electronic MMDs (eMMDs), use audible and/or visual signals to prompt the patient when to take medication, dispense medications, give instructions to the patient, and contact a caregiver (mobile Internet or text to a carer) as needed. Aim: To systematically review the literature on the use of eMMDs, to determine what evidence for their effectiveness is available. Methods: A comprehensive literature search of 10 databases, plus an Internet search and hand searching was conducted, using the MeSH terms reminder systems/patient compliance/medication adherence. There were no date restrictions. Inclusion criteria were patients in any community setting, in any country and with no restrictions of age, gender, ethnicity or medical condition, using an eMMD. Peer‐reviewed quantitative or qualitative studies of any design were included. Results: Of 805 abstracts identified and 99 full text papers retrieved, six met the inclusion criteria. Five of the studies reported adherence to medication regimes; one reported design factors to improve adherence. Adherence varied by the context of the reminders, the target group and usability of the devices. The studies were small scale and only one was a well conducted randomised controlled trial. Conclusion: Overall methodological quality of the studies was poor. Although positive effects on adherence were reported further, rigorously conducted, studies are needed to inform the use of eMMDs.